Linguistic problems of translating Indonesian popular lyrics of cover songs into English - Tira Nur Fitria (Universitas Bengkulu, 2022)
Translation results can be influenced by linguistic aspects. The objective of this study is to investigate several kinds of linguistic problems in the translation of Indonesian popular lyrics’ cover-songs from Indonesian into English. This study applies descriptive qualitative research. This research uses the document to collect data. The document used is cover songs from several popular singers and bands such as Andmesh Kamaleng, Anneth, Budi Doremi, Nineball, and Christian Bautista. There are seven popular lyrics’ cover songs that have been analyzed. The result analysis shows that translation songs activities cannot be separated from linguistic problems as in morphological, syntactical, phonological, and semantic. Morphologically, the problem is in the difference of the grammatical system related to singular and plural nouns. In phonological, the problem is in the differences between Indonesian and English syllables. As a result, the differences cause a different pronunciation and produce a different number of syllables. Syntactically, the problem is in constructing sentence elements. In a sentence, both in Indonesian and English at least will need a subject and a predicate orderly. Semantically, the problem is related to the meaning contained in a word or sentence, but equivalence may occur in translating to achieve an adequate degree of equivalence. When translating a song, a translator must pay close attention to the many components that contribute to the creation of a full product song. These components include song lyrics or text, as well as musical elements like melody and rhythm. In its formulation, the song lyric is a language that is not isolated from the musical principles such as the song's rhythm, melody, and harmony. In song translation, the sense and facts of the source texts are often changed. Therefore, the translator is faced with a choice of whether or not to translate such a lyric.